2021
DOI: 10.1101/2021.12.08.21267502
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement of SARS-CoV-2 antigens in plasma of pediatric patients with acute COVID-19 or MIS-C using an ultrasensitive and quantitative immunoassay

Abstract: Background: Detection of SARS-CoV-2 antigens in blood has high sensitivity in adults with acute COVID-19, but sensitivity in pediatric patients is unclear. Recent data suggest that persistent SARS-CoV-2 spike antigenemia may contribute to multisystem inflammatory syndrome in children (MIS-C). We quantified SARS-CoV-2 nucleocapsid (N) and spike (S) antigens in blood of pediatric patients with either acute COVID-19 or MIS-C using ultrasensitive immunoassays (Meso Scale Discovery). Methods: Plasma was collected f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…As anticipated, a higher N antigen concentration was observed per GE in comparison to S antigen concentration, which has also been shown in plasma. 17,18 These results support the focus on N antigen for RDTs and overall correlation of antigen concentration with genome copy number 9,19,20 .…”
Section: Discussionsupporting
confidence: 72%
“…As anticipated, a higher N antigen concentration was observed per GE in comparison to S antigen concentration, which has also been shown in plasma. 17,18 These results support the focus on N antigen for RDTs and overall correlation of antigen concentration with genome copy number 9,19,20 .…”
Section: Discussionsupporting
confidence: 72%
“…A recent study demonstrated that persistence of SARS-CoV-2 in the gastrointestinal tracts of patients with MIS-C was associated with a breakdown of mucosal integrity and subsequent spike protein antigenemia and hyperinflammation [ 27 ]. While this explanation could correspond with the prominent gastrointestinal symptoms observed in MIS-C, the finding of SARS-CoV-2 antigenemia has not been universal [ 28 ]. The reasons why antigenemia may trigger delayed but not acute systemic hyperinflammation are similarly unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing interest in the utility of the detection of viral protein antigens in the blood, which are detectable within 2 weeks of symptom onset [27][28][29][30] and are quantifiable even in patients with mild or minimal symptoms [28][29][30][31]. However, there are currently limited studies of how SARS-CoV-2 viral antigen detection in the blood is related to disease severity and outcomes [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%